If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-5(-2x-6)=4(x+11)
We move all terms to the left:
-5(-2x-6)-(4(x+11))=0
We multiply parentheses
10x-(4(x+11))+30=0
We calculate terms in parentheses: -(4(x+11)), so:We get rid of parentheses
4(x+11)
We multiply parentheses
4x+44
Back to the equation:
-(4x+44)
10x-4x-44+30=0
We add all the numbers together, and all the variables
6x-14=0
We move all terms containing x to the left, all other terms to the right
6x=14
x=14/6
x=2+1/3
| 13q-6q=7 | | 12r-11r=6 | | 12y-11y=16 | | 8g-3g=10 | | 10z-z=9 | | 7=19−3m | | -6=1+n-4 | | 11−3t=5 | | 1/2a+1=90 | | 11−2q=3 | | 0.75×n=15 | | 12−3y=3 | | w5-23=8 | | 10−2k=2 | | 3(1-3x)=8×+14 | | 4(2r+1)-(2r-5)=29 | | 31-7x=16+8x | | 28-2x=14+12x | | 13y=-25 | | 3+1/2n=15* | | 12−3u=6 | | 1=3z−5 | | (1/2)(5x+10)=6 | | F(n)=2-3n | | 4(x-4)^+17=85 | | -32+17x=-1x | | (1/5)(5x+10)=6 | | h-2+15=32 | | 24-u=7u | | 7x^2-9x-68=0 | | 3x-22=3x-420 | | 0=2x^2+6x-24x |